(untitled) (Research, Society and Development, 2022)
The aim of this study was identifying the root rot causal agents in cassava, cv Rosinha, in Alagoas state, Brazil. Pathogen species were studied, which are responsible for root rot in cassava, through isolation, morphological characterization and pathogenicity confirmation. Fusarium sp was emphasized among other isolated genera, which is pathogenic to cassava roots and plants. The phylogenetic study was based on the ITS region of the constructed DNA, using the ‘‘maximum Likelihood Tree’’ method, with a base of 1000 “bootstrap” replicas, what showed 100% of genetic similarity to Fusarium falciforme.